Answer:
The trigonometric equation (sin Θ − cos Θ)^2 − (sin Θ + cos Θ)^3 can be simplified by:Using x for Θ: (sinx - cosx)^2 - (sinx + cosx)^2 = (sin^2 x - 2sinxcosx + cos^2 x) - (sin^2 x + 2sinxcosx + cos^2 x) = - 2 sinx cosx - 2 sinx cosx = - 4 sinx cosx = - 2sin(2x)
Step-by-step explanation:
Step-by-step explanation:
Identify the method that will be used to solve for x for each equation.
4x=20 division property fo equality
x-11=9 addition property of eqaulity
5x+6x=22 Combining Like terms
5(x-2)=30 distibute property
HOPE THIS HELPS!!!!!!!!
//////////////////////////////////////////////////////////////////////////////////////////////////////////////
Answer:
(4×-3)(2x-1)
Step-by-step explanation:
8x²-10x+3
8x²-4x-6x+3
4x(2x-1)-3(2x-1)
(4×-3)(2x-1)
10.417 rounded to the nearest hundredth is 10.42
Hope it helps!